Aspergillus terreus variant TB21 wet biomass optimized by in-situ transesterification for biodiesel production - Bed, Rashmi K.; Kumar, V. Ravi; RaviKumar, Ameeta (AMB Express, 2025)
The oleaginous fungus, Aspergillus terreus when subjected to random chemical mutagenesis led to isolation of TB21 variant with improved lipid content (78.1%) as compared to wild type (49.8%). The fungal wet biomass grown on sugarcane bagasse hydrolysate (SCBH) was subjected to one-step in-situ (direct) acid transesterification to optimize its conversion to biodiesel using a 2-level factorial statistical design of experiments. The process optimization revealed that wet biomass and methanol were the most significant factors and in a short reaction time period of 5 min with low methanol: wet biomass ratio (10:1) influenced FAME production Statistical optimization studies showed that TB21 exhibited a higher FAME content of 76.5 and 38.1% (w/w) from wet and dry biomass, respectively when compared to wild type (48.1 and 24.5%). FAME productivity (0.55-1 h-1) and a yield (66 gL-1) were achieved when TB21 was grown on SCBH for 120 h at 30 degrees C. The FAME profile from the wet biomass of TB21 grown on SCBH had desirable amounts of saturated (77.7%), monounsaturated (7.2%), and polyunsaturated (2.4%) methyl esters. Physico-chemical properties of TB21-derived biodiesel were determined, namely, density(0.88 g cm-3), kinematic viscosity (4.1 mm s-2), iodine value (96.82), cetane number (55.31), free fatty acid content (0.15%), total acid number (0.3 NaOH mg g-1), meeting international (ASTM D6751, EN 14214) and Indian (IS 15607) standards. Thus, the direct one-pot in situ transesterification reaction using wet biomass of variant TB21 strain showed improved production and quality of biodiesel with potential large scale application using the low-cost substrate (SCBH).
Keywords: Aspergillus Terreus; Biodiesel; In situ transesterification; Mutant; Statistical optimization; Wet biomass